PENDAMPINGAN UMKM: COACHING CLINIC PEMBUATAN LAPORAN KEUANGAN SEDERHANA DENGAN APLIKASI SI-APIK (Jurnal Pengabdian Masyarakat AbdiMas, 2022)
This Community Service is part of the assistance activities of MSMEs actors who are members of the Jakpreneur in cooperation with the DKI Jakarta Provincial PPKUKM Office. Mentoring in the form of Coaching Clinic aims to help MSMEs actors can make simple Financial Statements that are in accordance with accounting standards or rules. Si APIK application provided by Bank Indonesia for MSME actors is used in mentoring activities to help MSMEs actors. The result of this Community Service activity is the ability of MSMEs actors to use the SI APIK application to produce Financial Statements such as Balance Sheets and Income Statements in accordance with The Standards of Small, Micro, and Medium Entity Financial Accounting (SAK-EMKM) where before this activity was carried out financial recording was only limited to recording receipts and cash expenditures.